The common properties and the heterogeneity of dermal fibroblast subpopulations. - Makarchuk O.I. (Морфологія, 2007)
Dermal fibroblasts are a dynamic and diverse population of cells whose functions in skin in many respects remain unknown. Normal adult human skin contains at least three distinct subpopulations of fibroblasts, which occupy unique niches in the dermis. Fibroblasts from each of these niches exhibit distinctive differences when cultured separately. Specific differences in fibroblast histophysiology are evident in papillary dermal fibroblasts, which reside in the superficial dermis, and reticular fibroblasts, which reside in the deep dermis. Both of these subpopulations of fibroblasts differ from the fibroblasts that are associated with hair follicles. Fibroblasts engage in fibroblast-epidermal interactions during hair development and in interfollicular regions of skin. They also play an important role in cutaneous structural transformations.